Mental Health Outcomes and Their Correlates in The Post-COVID-19 Era Among University Students and Staff in Indonesia - Setiyadi, Noor Alis; Chakim, Irfanul; Rifki Fauzi, Ekha; Sri Purwanti, Okti; Andajani, Sari; Lianawati; Joseas Conwi, Lord; Sornlorm, Kittipong (National Journal of Community Medicine, 2025)
Background: The COVID-19 pandemic has profoundly affected global health, particularly mental health in academic communities. While its impact on mental health is well-documented, studies on the post-pandemic "new normal" remain scarce. This study examines the prevalence and factors linked to anxiety, depression, and QoL among Indonesian university students, lecturers, and staff post-pandemic. Methods: This cross-sectional study examines the impact of risk factors on anxiety, quality of life, and depression among university students, staff, and faculty post-Covid-19 vaccination. An online website link was sent to the participants comprising instruments such as PHQ-2, WHOQOL-BREF and GDS. Chi-square tests were used for bivariate analysis, and multivariate logistic regression modelled associated factors. Results: Poor QoL, depression, and anxiety were reported by 51.68%, 40.83%, and 44.19%, respectively. Unmarried individuals and those without a COVID-19 booster had higher odds of poor QoL (AOR: 3.32; 1.62). Unmarried individuals also faced greater depression risk (AOR: 2.56), while females and those with unvaccinated family members were more prone to anxiety (AOR: 2.42; 1.50). Conclusion: This study highlights mental health challenges post-pandemic, especially for those with incomplete vaccination and limited social support. It emphasizes the need for targeted interventions and complete vaccination to boost resilience in academic settings.